Pseudocnidae of ribbon worms (Nemertea): ultrastructure, maturation, and functional morphology - Magarlamov,Timur Yu; Turbeville,James M.; Chernyshev,Alexei V. (PeerJ, 2021)
The fine structure of mature pseudocnidae of 32 species of nemerteans, representatives of 20 genera, six families, and two classes was investigated with scanning and transmission electron microscopy. Pseudocnidae are composed of four layers (cortex, medulla, precore layer, and core) in most species investigated, but the degree of development and position of each layer can vary between different species. The secretion products comprising immature pseudocnidae segregate into separate layers: a thin envelope, which subsequently separates into the cortex and medulla and an extensive internal layer. We distinguish two pseudocnida types: type I is characterized by a two-layered core and type II by a three-layered core. Type I pseudocnidae are present in archinemertean species, Carinoma mutabilis, and in all pilidiophoran species, except Heteronemertea sp. 5DS; type II pseudocnidae occur in all studied species of Tubulanidae and the basal Heteronemertea sp. 5DS. Based on the structure of the discharged pseudocnidae observed in eleven species of palaeonemerteans and in eight species of pilidiophorans, we distinguish three different mechanisms (1–3) of core extrusion/discharge with the following characteristics and distribution: (1) the outer core layer is everted simultaneously with the tube-like layer and occurs in type I pseudocnidae of most species; (2) the extruded core is formed by both eversion of the outer core layer and medullar layer, and occurs in type I pseudocnidae of Micrura cf. bella; (3) the eversion of the outer core layer begins together with the core rod and core rod lamina and occurs in type II pseudocnidae. Morpho-functional comparison with other extrusomes (cnidae, sagittocysts, rhabdtites, and paracnids) confirm that pseudocnidae are homologous structures that are unique to nemerteans.
Keywords: Extrusomes; Pseudocnidae; Ultrastructure; Proboscis; Palaeonemertea; Pilidiophora